KAJIAN LAMA FERMENTASI TERHADAP KADAR ALKOHOL TAPE KETAN HITAM (Oryza sativa glutinosa) SEBAGAI PENGEMBANGAN LEMBAR KERJA SISWA PADA KONSEP BIOTEKNOLOGI KONVENSIONAL KELAS XII SMA - Weny Andriani Andriani; Darmawati '; Sri Wulandari Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to determine the sudy of fermentation’s length of black sticky tape alcohol content in March to May 2015, for development of Student Worksheet of biology at the concept of conventional biotechnology class XII in Senior High School. The research was conducted with 2 phases of field research and the development of learning worksheets. Experimental research was conducted by using non factorial completely randomized design consisting of 5 treatments and 3 replicates in order to obtain 15 experimental design. If there isa real test of it will proceed further test DMRT. The observed parameters include alcohol content, temperature, pH and organoleptic texture, smell, color and flavor. The result showed that the fermentation timesignificantly influence the alcohol content of black sticky tape. 120 hours fermentation time was the best fermentation time, which can reach the highest alcohol content with an average of 0,23%. The temperature generated of the black sticky tape ranges between 30,5oC-33,6 oC. pH generated of the black sticky tape ranges between 4,64-3,54. Whereas for organoleptic texture, smell, color and flavor of black sticky tape panelists preferred is the treatment of fermentation 72 hours. Results of research for the development of student worksheets of biology at the concept of conventional biotechnology class XII in Senior High School Keywords: Fermentation’s length, black sticky tape, Student Worksheet.